THE ENGLISH AND SASAK DERIVATIONAL MORPHEME ON STUDY COMPARATION - Sugianto Sugianto; Kamarudin Kamarudin; Muhamad Sarifuddin (Cordova Journal : languages and culture studies, 2019)
The researcher is aimed at comparing the derivational morphemes exist in sasak language and English language. This comparison leads into the construction of new words variation to build a complete sentence bot in English and in Sasaknese. By comparing the derivational morphemes between Sasak language and English language, some similarities and differences of both languages truly revealed. The similarities between them brought the easiness to the students of Sasak while learning English. Conversely, the differences caused difficulties the students who are learning English. The comparison between these two languages derivational morphemes hopefully brought some positive effects on students’ English mastery particularly the mastery of vocabularies and the process that made them up. An in-depth study on how those derivational morphemes in both languages are different were conducted for the sake of the data complete of the study. The interview section of the research was conducted among the experts of those two languages to support the filed data needed in the research. The data collected through the interview process istranscribed and reduced based on research need for the sake of answering the research question. The research conclusion said that some derivational morphemes exited in the Sasak were also found in English derivational morpheme process which then translated into some easiness can be found during English study process of the students who speak Sasak as their first language.